Brill's Companion to Euripides (2 vols) - Markantonatos, Andreas (Brill's Companions to Classical Studies., 2020)
Brill's Companion to Euripides offers 49 specially commissioned essays from leading international scholars which give critical examinations of the progress and direction of numerous wide-ranging debates about various aspects of Euripidean drama. Each chapter, as well as covering a wide diversity of thematic angles, provides readers with an authoritative and state-of-the-art survey of current thinking and research in a particular subject area. Recent advances in scholarship have raised new questions about Euripides and Attic drama, and have overturned some long-standing assumptions and canons. Besides presenting a comprehensive and authoritative guide to understanding Euripides and his masterworks, this companion provides scholars and students with compelling fresh perspectives upon a broad range of issues in the rapidly evolving field of Euripidean studies.